Pemilihan Supplier Bahan Baku Dengan Metode AHP Study Kasus PT. Nara Summit Industry, Cikarang - Puji Astuti - STMIK Nusa Mandiri Jakarta (Universitas Bina Sarana Informatika, 2016)
Abstract—Analytical methods Hierarcy Process (AHP) is a decision support model will elaborate multi-factor problem or a complex multi-criteria into a hierarchy, Saaty (1993). Decisions can be taken based on the results of the respondents, namely the provision of a questionnaire containing a comparison between the criteria and alternatives as the calculation in the selection of suppliers to the decisions involved therein, which will be the result of the acquisition of the questionnaire will be calculated by using the tools super decision in the processing of the data by the method of AHP. Supplier of raw materials that exist on the PT. Nara Summit Industry, Cikarang there are 4 different suppliers with the same raw material. Therefore the calculation by using AHP. There is a final value that has been processed using super decision tools to the value at supplier01 (S01) is 0.19146, the value of the supplier02 (S02) 0.17739, supplier03 (S03) 0.17538 and the supplier04 (S04) 0.45576. Seen that supplier4 (S04) has the highest value, then the elected supplier of raw materials for PT. Nara Summit Industry, Cikarang is Supplier4 (S04)Keywords – Decision Support System, Methode AHP, Selection Suppliers Of Raw Materials Abstrak – Metode Analytical Process Hierarcy (AHP) adalah model pendukung keputusan akan menguraikan masalah multi-faktor atau kompleks multi-kriteria dalam hirarki, Saaty (1993). Keputusan dapat diambil berdasarkan hasil dari responden, yaitu penyediaan kuesioner yang berisi perbandingan antara kriteria dan alternatif sebagai perhitungan dalam pemilihan pemasok untuk keputusan yang terlibat di dalamnya, yang akan menjadi hasil dari akuisisi kuesioner akan dihitung dengan menggunakan alat keputusan yang super dalam pengolahan data dengan metode AHP. Pemasok bahan baku yang ada pada PT. Nara Summit Industry, Cikarang ada 4 pemasok yang berbeda dengan bahan baku yang sama. Oleh karena itu perhitungan dengan menggunakan AHP. Ada nilai akhir yang telah diolah menggunakan alat keputusan super untuk nilai di supplier01 (S01) adalah 0,19146, nilai supplier02 (S02) 0,17739, supplier03 (S03) 0,17538 dan supplier04 (S04) 0,45576. Terlihat bahwa supplier4 (S04) memiliki nilai tertinggi, maka pemasok terpilih bahan baku untuk PT. Nara Summit Industry, Cikarang adalah Supplier4 (S04)Kata Kunci : SPPK, Sistem Pengambilan Keputusan